Synthesis, Applications, and Prospects of Graphene Quantum Dots: A Comprehensive Review. Issue 2 (22nd September 2021) - Ghaffarkhah, Ahmadreza; Hosseini, Ehsan; Kamkar, Milad; Sehat, Ali Akbari; Dordanihaghighi, Sara; Allahbakhsh, Ahmad; van der Kuur, Colin; Arjmand, Mohammad
Abstract: Graphene quantum dot (GQD) is one of the youngest superstars of the carbon family. Since its emergence in 2008, GQD has attracted a great deal of attention due to its unique optoelectrical properties. Non‐zero bandgap, the ability to accommodate functional groups and dopants, excellent dispersibility, highly tunable properties, and biocompatibility are among the most important characteristics of GQDs. To date, GQDs have displayed significant momentum in numerous fields such as energy devices, catalysis, sensing, photodynamic and photothermal therapy, drug delivery, and bioimaging. As this field is rapidly evolving, there is a strong need to identify the emerging challenges of GQDs in recent advances, mainly because some novel applications and numerous innovations on the ease of synthesis of GQDs are not systematically reviewed in earlier studies. This feature article provides a comparative and balanced discussion of recent advances in synthesis, properties, and applications of GQDs. Besides, current challenges and future prospects of these emerging carbon‐based nanomaterials are also highlighted. The outlook provided in this review points out that the future of GQD research is boundless, particularly if upcoming studies focus on the ease of purification and eco‐friendly synthesis along with improving the photoluminescence quantum yield and production yield of GQDs. Abstract : This review provides a comparative and balanced discussion on various perspectives of graphene quantum dots (GQDs). First, the most exciting properties, synthesis and modification strategies, analytical characterizations, and applications of GQDs are presented. Then, the current challenges and future prospects of these emerging carbon‐based nanomaterials are highlighted.